Implementation of Mass Cytometry for Immunoprofiling of Patients with Solid Tumors - Poláková, Ingrid; Pelák, Ondřej; Thürner, Daniel; Pokrývková, Barbora; Tachezy, Ruth; Kalina, Tomáš; Šmahel, Michal (Journal of immunology research, 2019)
Monitoring immune responses to solid cancers may be a better prognostic tool than conventional staging criteria, and it can also serve as an important criterion for the selection of individualized therapy. Multiparametric phenotyping by mass cytometry extended possibilities for immunoprofiling. However, careful optimization of each step of such method is necessary for obtaining reliable results. Also, with respect to procedure length and costs, sample preparation, staining, and storage should be optimized. Here, we designed a panel of 31 antibodies which allows for identification of several subpopulations of lymphoid and myeloid cells in a solid tumor and peripheral blood simultaneously. For sample preparation, disaggregation of tumor tissue with two different collagenases combined with DNase I was compared, and removal of dead or tumor cells by magnetic separation was evaluated. Two possible procedures of barcoding for single-tube staining of several samples were examined. While the palladium-based barcoding affected the stability of several antigens, the staining with two differently labeled CD45 antibodies was suitable for cells isolated from a patient's blood and tumor. The storage of samples in the intercalation solution for up to two weeks did not influence results of the analysis, which allowed the measurement of samples collected within this interval on the same day. This procedure optimized on samples from patients with head and neck squamous cell carcinoma enabled identification of various immune cells including rare subpopulations.
Keywords: Immunophenotyping; průtoková cytometrie; imunofenotypizace; antigeny CD45; taxonomické DNA čárové kódování; Lymphocytes; Deoxyribonuclease I; myeloidní buňky; separace buněk; monoklonální protilátky; Leukocyte Common Antigens; Single-Cell Analysis; lymfocyty; Antibodies, Monoclonal; deoxyribonukleasa I; Collagenases; palladium; Cell Separation; Palladium; Flow Cytometry; Neoplasms; Humans; nádory; Myeloid Cells; analýza jednotlivých buněk; kolagenasy; DNA Barcoding, Taxonomic; lidé